2005
DOI: 10.1117/12.624676
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of adaptive-stiffening and shape-control SMA hybrid composites

Abstract: The usage of shape memory materials has extended rapidly to many fields, including medical devices, actuators, composites, structures and MEMS devices. For these various applications, shape memory alloys (SMAs) are available in various forms: bulk, wire, ribbon, thin film, and porous. In this work, the focus is on SMA hybrid composites with adaptive-stiffening or morphing functions. These composites are created by using SMA ribbons or wires embedded in a polymeric based composite panel/beam. Adaptive stiffenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The available literature shows that various configurations of cantilever beams under different loading conditions and actuated by internally embedded/bonded or externally connected SMA actuators [13][14][15] have already been investigated extensively as a composite structure and elastica column. Detailed finite element analyses of various composite structures with embedded SMA actuators have already been documented elsewhere [13,[16][17][18] and hence beyond the scope of this paper. Pelton et al [19] tested various superelastic micro-tubes experimentally and with finite element method (FEM) and found that, at larger deflections, the model fits the experimental data extremely well.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature shows that various configurations of cantilever beams under different loading conditions and actuated by internally embedded/bonded or externally connected SMA actuators [13][14][15] have already been investigated extensively as a composite structure and elastica column. Detailed finite element analyses of various composite structures with embedded SMA actuators have already been documented elsewhere [13,[16][17][18] and hence beyond the scope of this paper. Pelton et al [19] tested various superelastic micro-tubes experimentally and with finite element method (FEM) and found that, at larger deflections, the model fits the experimental data extremely well.…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al (2012) explored the parameters affecting the deflection of a curved structure and found that higher eccentricity and lower thickness lead to higher deflection, while Zhou and Lloyd (2009) showed that a matrix with lower structural rigidity leads to higher deflection by comparing the deflection of carbon/epoxy and E-glass/epoxy matrixes. Stiff matrixes such as glass/epoxy have also been used (Gao et al, 2006; Lu et al, 2009; Sun and Sun, 1995), and Wang et al (2008) found that a thin latex matrix was capable of a larger deformation compared to a thicker silicone matrix. Ryu et al (2011) proposed a matrix made of alternating glass fiber–reinforced plastic and silicone rubber to increase deflection of the actuation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the choice of truss elements allows to use a 1D SMA constitutive law. Differently from the recent works by Gao et al (2005Gao et al ( , 2006, the present FEM is actually 2D. Indeed, it does not require any mesh refinement along the plate thickness in order to model SMA wires embedded off the plate midplane, so reducing the number of nodal degrees of freedom and improving simplicity and computational efficiency.…”
Section: Sma Hybrid Composite Plate Modelmentioning
confidence: 99%
“…3. The SMA elements and the way they interact with the host structure are modeled directly and separately from the structure itself (Lagoudas and Tadjbakhsh, 1993;Lee et al, 1999;Gao et al, 2006).…”
Section: Sma Hybrid Composite Plate Modelmentioning
confidence: 99%